Analysis of Household Income in Poland by Regions Based on Selected Income Distribution - Trzcińska, Kamila (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
Research on income distributions focuses mainly on attempts to match theoretical distributions to the empirical income distribution and on the analysis of these distributions. The analysis results show that three‑parameter models very well approximate the income distribution of many countries. The Daguma distribution is recognised in the literature on income research as one of the best three parameter income distribution models. In 2010 Zenga proposed a new three‑parameter model for economic size distribution which possesses interesting statistical properties. The aim of this paper is to use the Dagum and Zenga model to analyze the distribution of Polish household income by regions. The D’Addario invariant methods and the maximum likelihood method were used to estimate the density function parameters. The calculations presented in the paper has been based on the individual data coming from the random sample obtained within the Household Budget Survey by regions by the Central Statistical Office in 2016. The article presents income inequality measures based on the considered models. The results of the calculations confirm that Zenga distribution is a good income distribution model which can be applied to analyze the income households of the Polish population.